Comparative Antioxidant Activity and Brine Shrimp Lethality of Green Tea and Black Tea Extracts† - V. Krishnaraju, Alluri; Sundararaju, Dodda; V.N. Rao, Tayi; Vanisree, Munabagal; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Aqueous extracts of green tea and black tea have shown strong antioxidant activity in nitro blue tetrazoliurn (NBT) photoreduction method and 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging activity. Green tea extracts, however, showed better antioxidant activity compared to the extracts of black tea. The antioxidant activity of these extracts has increased further in ethyl acetate soluble fractions. The activity corroborated well with the content of polyphenols present in these extracts. Aqueous extract of green tea has also shown brine shrimp lethality.